Structural, Technical and Petrographic Analysis of Bullae from the Samaria Papyri. (June 2015) - Gurwin, Shira; Goren, Yuval; Lipschits, Oded
Abstract : Twenty-two clay bullae associated with mid-4th century BCE Samaria Papyri from the cave of Wadi Daliyeh were subjected to structural, technical and petrographic examination. Results suggest that the bullae were all made in the Samaria region from several types of local soils. The technology and function of the bullae differ from those of earlier (Iron Age) Judahite bullae.